GENDER EQUALITY IN THE EDUCATION SYSTEM OF AZERBAIJAN REPUBLIC - Babayeva , Gunay (Collection of scientific papers «ΛΌГOΣ», 2022)
Republic of Azerbaijan is developing rapidly in all areas in the 21st century notable progress such as protection of human rights, especially gender equality, ensuring and protecting children’s rights etc. Education, social, culture, economics, science, production, gender equality in diplomacy, employment and other areas ensuring representation and combating gender discrimination is a major part of government policy is one of the main areas. Both in national legislation and in international gender equality is protected in matters arising from contracts and practices regarded as a top priority.